2016
DOI: 10.1016/j.pvr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection in cervical neoplasia attributed to 12 high-risk human papillomavirus genotypes by region

Abstract: BackgroundWe estimated the proportion of cervical intraepithelial neoplasia (CIN) cases attributed to 14 HPV types, including quadrivalent (qHPV) (6/11/16/18) and 9-valent (9vHPV) (6/11/16/18/31/33/45/52/58) vaccine types, by regionMethodsWomen ages 15–26 and 24–45 years from 5 regions were enrolled in qHPV vaccine clinical trials. Among 10,706 women (placebo arms), 1539 CIN1, 945 CIN2/3, and 24 adenocarcinoma in situ (AIS) cases were diagnosed by pathology panel consensus.ResultsPredominant HPV types were 16/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
4
30
0
1
Order By: Relevance
“…Although HPV 16 was the most prevalent genotype among patients with cervical disease, other HR‐HPV genotypes targeted by the nonavalent HPV vaccine were also detected in many patients with CIN2, CIN3, and ICC. Indeed, HR‐HPV genotypes 31, 33, 45, 52, and 58 were detected in 34.3% of CIN2, 33.3% of CIN3, and 19.4% of ICC occurrences; these rates were similar to those observed in other studies . The high proportion of ICC and CIN2/3 with HPV 16, 18, 31, 33, 45, 52, or 58 in Portugal appeared to be related to the high prevalence of HPV 31, 33, and 58.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although HPV 16 was the most prevalent genotype among patients with cervical disease, other HR‐HPV genotypes targeted by the nonavalent HPV vaccine were also detected in many patients with CIN2, CIN3, and ICC. Indeed, HR‐HPV genotypes 31, 33, 45, 52, and 58 were detected in 34.3% of CIN2, 33.3% of CIN3, and 19.4% of ICC occurrences; these rates were similar to those observed in other studies . The high proportion of ICC and CIN2/3 with HPV 16, 18, 31, 33, 45, 52, or 58 in Portugal appeared to be related to the high prevalence of HPV 31, 33, and 58.…”
Section: Discussionsupporting
confidence: 85%
“…Worldwide, approximately 90% of cervical cancers are attributed to HPV genotypes 16, 18, 31, 33, 45, 52, or 58 . Moreover, HPV 6, 11, 16, 18, 31, 33, 45, 52, and 58 are associated with 78% and 91% of CIN2 and CIN3 occurrences, respectively . In Europe, HPV 16 and 18 account for approximately 72.8% of all cervical cancers and 45.5% of high‐grade cervical dysplasia, whereas HPV genotypes targeted by the nonavalent vaccine account for 89% of cervical cancers and 82.3% of high‐grade cervical lesions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two largest prior studies, with 96 and 61 cases, were conducted in the Netherlands; these identified HPV16/18 in 79 and 94% of AIS cases (41 and 34% HPV16, 43 and 66% HPV18) . Four additional studies conducted in a variety of settings, with <50 cases each, also found HPV16/18 in the vast majority of AIS cases (ranging from 85% to 96%, with 51–71% HPV16 and 36–39% HPV18) …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reports indicate that the HPV types identified in CIN and AIS differ. While HPV16 is the most common type in both AIS and CIN lesions, data from several small studies found HPV18 more frequently in AIS than CIN lesions …”
Section: Introductionmentioning
confidence: 98%